2020
DOI: 10.2147/dmso.s257736
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Hypertriglyceridemic Waist Phenotype and Increased Urinary Albumin–Creatinine Ratio in Chinese Adults: The REACTION Study</p>

Abstract: The hypertriglyceridemic waist (HTGW) phenotype can predict cardiovascular disease (CVD) risk. Additionally, strong evidence indicates that elevated urinary albumincreatinine ratio (UACR) is associated with increased prevalence of CVD. However, few studies have explored the association between the HTGW phenotype and UACR. Patients and Methods: In this cross-sectional descriptive study, a total of 40,674 subjects (28,562 women and 12,112 men older than 40 years) were recruited from seven different geographic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…The current finding on the increased risk of CKD among HTGW individuals were consistent with several previous studies 15 , 16 , 18 , 20 , 21 , 23 . For example, a cross-sectional study conducted in China showed that participants with HTGW phenotype were more likely to have CKD (OR 2.09, 95% CI 1.26 to 3.45) 15 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current finding on the increased risk of CKD among HTGW individuals were consistent with several previous studies 15 , 16 , 18 , 20 , 21 , 23 . For example, a cross-sectional study conducted in China showed that participants with HTGW phenotype were more likely to have CKD (OR 2.09, 95% CI 1.26 to 3.45) 15 .…”
Section: Discussionsupporting
confidence: 93%
“…Instead, we used 85 cm, which was considered an appropriate cut-off in Chinese women for central obesity 26 . Similarly, several studies used 2.0 mmol/L to define high triglycerides 15 , 18 , 19 , 21 , 22 , while we used the cut-off of 1.7 mmol/ L, which was recommended to define metabolic syndrome in Chinese 28 . Also, previous research has shown that triglyceride levels above 1.7 mmol/L was already significantly associated with increased risk of CKD 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence indicates that obesity and CKD have increased in parallel worldwide and are positively correlated [12], and obesity, especially visceral obesity, is an important risk factor for CKD [3,5,6,7]. Visceral obesity has been reported to be associated with IR, dyslipidemia, nonalcoholic fatty liver disease, metabolic syndrome, hyperuricemia, diabetes, hypertension, and CVD events [5,6,8,9], all of which are involved in the pathogenesis of CKD [3,4,10]. Direct measurement of visceral adipose tissue by imaging techniques, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with subcutaneous adipose tissue, visceral adipose tissue is more strongly associated with cardiometabolic risks [5]. Visceral adipose tissue secretes several proinfammatory cytokines such as C-reactive protein (CRP), interleukine-6 (IL-6), and distinct atherogenic lipoprotein pro les, contributes to the change in adipocytokines such as adiponectin, leptin, resistin, and omentin-1, which lead to subclinical in ammation, oxidative stress, insulin resistance (IR), and endothelial dysfunction, and subsequently, induces kidney structure and function changes such as glomerular sclerosis and increased albuminuria, and ultimately result in renal dysfunction [5,7,8,9]. Body mass index (BMI) is the most frequently used index in the assessment of adiposity in clinical practice, but lacks discriminatory power between lean vs. adipose tissue, or between subcutaneous and visceral fat, and also lacks the ability to track over time changes in the lipid compartment [10].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Hypertriglyceridemic waist (HTGW) phenotype, defined as increased WC with an elevated TG level, is cheap and easy to determine. It is commonly used to screen for gestational 16 or type2 17 diabetes mellitus, as well as for hypertension, 18 increased urinary albumincreatinine ratio, 19 hepatic steatosis, 20 and cardiovascular disease. 21 Because OSA is associated with MS and many of the aforementioned diseases, we hypothesized that HTGW phenotype might predict the risk of OSA.…”
Section: Introductionmentioning
confidence: 99%